The role of adjuvant therapy in pT4N0 laryngectomized patients: Multicentric observational study. Issue 1 (17th October 2022) - Mattioli, Francesco; Serafini, Edoardo; Lo Manto, Alfredo; Mularoni, Francesca; Abeshi, Andi; Lionello, Marco; Ferrari, Marco; Paderno, Alberto; Lancini, Davide; Mattavelli, Davide; Confuorto, Gennaro; Marchi, Filippo; et al.
Abstract: Background: To retrospectively evaluate oncological outcomes in two groups of patients with pT4aN0 glottic SCC treated with total laryngectomy (TL) and neck dissection (ND) who underwent postoperative radiotherapy or exclusive clinical and radiological follow‐up. Methods: It includes patients with pT4N0 glottic SCC who underwent TL and unilateral or bilateral ND with or without PORT. Divided in two comparison groups: the first group underwent adjuvant RT (TL‐PORT); the second group referred to clinical and radiological follow‐up (TL). Results: PORT was associated with a better OS while no differences were found in terms of DSS. A better local control is achieved when PORT is administered while no differences in terms of regional and distant control rates were found. Bilateral ND positively impacts on the regional control while the PNI negatively impact the regional control. Conclusions: A tailored PORT protocol might be considered for pT4N0 glottic SCC treated with TL and ND, both considering the ND's extent and presence of PNI.